Bond characteristics and microwave dielectric properties of (Li0.5Ga0.5)2+ doped Mg2Al4Si5O18 ceramics. Issue 18 (15th December 2020) - Lou, Weichao; Song, Kaixin; Hussain, Fayaz; Liu, Bing; Bafrooei, Hadi Barzegar; Lin, Huixin; Su, Weitao; Shi, Feng; Wang, Dawei
Abstract: Cordierite ceramic is one kind of important electronic materials for radio frequency circuit. In this work, Mg2-x (Li0.5 Ga0.5 )x Al4 Si5 O18 (0 ≤ x ≤ 0.1) ceramics with pure cordierite phase, were successfully synthesized via the traditional solid state reaction method. The dependence of microwave dielectric properties on the crystal structure was analyzed in detail by the complex chemical bond theory (P–V-L theory) and classical dielectric polarizability theory. The dielectric constant ( ε r ) was mainly related to the density, bond ionicity and ionic polarizability of Mg2-x (Li0.5 Ga0.5 )x Al4 Si5 O18 ceramics. The quality factor ( Q  ×  f ) was in relationship to the lattice energy, atomic packing fraction and centrosymmetry of [Si4 Al2 O18 ] hexagonal ring in cordierite crystal structure. The temperature coefficient of resonant frequency ( τ f ) value was dominated by the bond energy and distortions of [MgO6 ] octahedron. The maximum values of Q  ×  f  = 50, 560 GHz and ε r  = 4.72 were obtained for undoped Mg2 Al4 Si5 O18 and Mg1.98 Li0.01 Ga0.01 Al4 Si5 O18, respectively.